The role of transcurrent intra-arc tectonics in the configuration of a volcanic arc - Tibaldi, A (Terra Nova, 1992)
Field investigations show that Plio‐Quaternary Mexican and Quaternary Ecuadorian volcanic arcs are coeval with intra‐arc transcurrent or transtensional tectonics with motions along faults parallel or subparallel to the arc. This relationship can also be observed in the Quaternary Kamchatka arc. These arcs have an anomalously wide distribution of volcanic centres which cannot be explained simply by a low dip in the subducting lithosphere. Comparison with the intra‐arc tectonics and geometry of other Quaternary arcs reveals that strike‐slip fault zones, parallel to the arc, favour magma rising in a broad surficial zone and may channel magma feeding mainly huge stratovolcanoes. Copyright © 1992, Wiley Blackwell. All rights reserved